Health-related quality of life and disability in patients with acute unilateral peripheral vestibular disorders - Petri,Maria (2017)
Abstract Introduction: Health-related quality of life is used to denote that portion of the quality of life that is influenced by the person's health. Objectives: To compare the health-related quality of life of individuals with vestibular disorders of peripheral origin by analyzing functional, emotional and physical disabilities before and after vestibular treatment. Methods: A prospective, non randomized case-controlled study was conduced in the ENT Department, between January 2015 and December 2015. All patients were submitted to customize a 36 item of health survey on quality of life, short form 36 health survey questionnaire (SF-36) and the Dizziness Handicap Inventory for assessing the disability. Individuals were diagnosed with acute unilateral vestibular peripheral disorders classified in 5 groups: vestibular neuritis, Ménière Disease, Benign Paroxysmal Positional Vertigo, cochlear-vestibular dysfunction (other than Ménière Disease), or other type of acute peripheral vertigo (as vestibular migraine). Results: There was a statistical significant difference for each parameter of Dizziness Handicap Inventory score (the emotional, functional and physical) between the baseline and one month both in men and women, but with any statistical significant difference between 7 days and 14 days. It was found a statistical significant difference for all eight parameters of SF-36 score between the baseline and one month later both in men and women; the exception was the men mental health perception. The correlation between the Dizziness Handicap Inventory and the SF-36 scores according to diagnostics type pointed out that the Spearman's correlation coefficient was moderate correlated with the total scores of these instruments. Conclusion: The Dizziness Handicap Inventory and the SF-36 are useful, proved practical and valid instruments for assessing the impact of dizziness on the quality of life of patients with unilateral peripheral vestibular disorders.